Development Of Analysis Methods Based On Scientific Approach And Risk-Based Approach In The Pharmaceutical Industry: Narrative Review - Fahdalis Alifrizqy Massi; Fajrini Adya Rizki Mokoagow; Siti Najma Bakari; Nur Ain Thomas; Faradila Ratu Cindana Mo'o (CV. AFDIFAL MAJU BERKAH, 2026)
The development of analytical methods and quality systems in the pharmaceutical industry is now shifting from the conventional trial and error approach to a systematic, scientific, and risk-based approach to meet international regulatory demands. This article aims to examine the effectiveness of implementing the concepts of Analytical Quality by Design (AQbD), Quality by Design (QbD), and various risk management instruments in improving product quality and operational efficiency in the pharmaceutical industry. Methods: This study is the result of a literature review of 15 scientific journals discussing analytical method development, process validation, product stability, and operational risk management. The analysis shows that the application of AQbD and QbD through parameters such as Analytical Target Profile (ATP) and Design of Experiments (DoE) can increase the robustness of analytical methods and reduce the risk of failures such as Out of Specification (OOS). The use of risk management tools such as Failure Mode and Effect Analysis (FMEA) has proven effective in identifying cross-contamination risks and distribution process failures. The integration of scientific and risk-based approaches has a significant positive impact in ensuring quality consistency, accelerating time-to-market, and supporting compliance with ICH guidelines (Q8, Q9, Q10, Q14).